2017
DOI: 10.1016/j.pbb.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential housing and novelty response: Protection and risk from locomotor sensitization

Abstract: High novelty seeking increases the risk for drug experimentation and locomotor sensitization. Locomotor sensitization to psychostimulants is thought to reflect neurological adaptations that promote the transition to compulsive drug taking. Rats reared in enrichment (EC) show less locomotor sensitization when compared to rats reared in isolation (IC) or standard conditions (SC). The current research study was designed to test if novelty response contributed locomotor sensitization and more importantly, if the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 79 publications
(113 reference statements)
3
13
0
Order By: Relevance
“…On the other hand, in our experimental conditions, declarative memory performance of p-IAD EE rats was not different from their SE counterparts’ one, suggesting that the abnormalities in declarative memory formation due to the perinatal intermittent exposure to alcohol are not rescued by the EE. Besides, the repeated exposure to environmental stimuli has been reported to decrease the incentive value of novelty (Cain et al, 2006 ; Garcia et al, 2017 ), suggesting that a lower interest in the novel object may explain its lower exploration by the EE offspring. Interestingly, our data show that EE mitigated the spatial learning and reference memory deficits induced by the perinatal intermittent alcohol paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in our experimental conditions, declarative memory performance of p-IAD EE rats was not different from their SE counterparts’ one, suggesting that the abnormalities in declarative memory formation due to the perinatal intermittent exposure to alcohol are not rescued by the EE. Besides, the repeated exposure to environmental stimuli has been reported to decrease the incentive value of novelty (Cain et al, 2006 ; Garcia et al, 2017 ), suggesting that a lower interest in the novel object may explain its lower exploration by the EE offspring. Interestingly, our data show that EE mitigated the spatial learning and reference memory deficits induced by the perinatal intermittent alcohol paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…The present data are consistent with and support previous studies pointing to the negative impact of losing EE on drug intake. Switching mice from EE to SE conditions caused an increase in cocaine rewarding properties (Nader et al, 2012 ), a marked depressive-like phenotype characterized by low mobility in the forced swim test (Smith et al, 2017 ), and increased locomotor responses to amphetamine and saline when compared with chronically EE housed animals (Garcia et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, present data are consistent, and complement previous studies reporting positive EE effects on repetitive compulsive-like behavior (Bechard and Lewis, 2016 ; Bechard et al, 2016 ). Thus, EE-housed rats switched to isolated conditions increased novelty-seeking responses in the inescapable novelty test (IEN; Garcia et al, 2017 ), switching rats from isolated to enriched conditions decreased novelty-seeking responses (Garcia et al, 2017 ), and housing rats in enriched conditions from weaning to adulthood reduced novelty-seeking behavior in the OF test and locomotor activity cages (de Carvalho et al, 2010 ). Strong evidence supports head dipping in HB as a valid novelty-seeking trait measure (Vaglenova et al, 2004 ; Abreu-Villaça et al, 2006 ; Kliethermes and Crabbe, 2006 ; Mateos-García et al, 2015 ), however, some authors have suggested that the number of head dips might be indicative of a neophobic, rather than neophilic, response (Brown and Nemes, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Limited literature exists that formally compares post-weaning social isolation effects between rat strains. However, after postweaning social isolation Lister Hooded rats exhibit hyperlocomotion in an open-field testan effect which is inconsistent in Sprague-Dawley rats (Garcia, Haddon, Saucier, & Cain, 2017;Green, Cain, Thompson, & Bardo, 2003;Leng, Feldon, & Ferger, 2004;Lukkes, Mokin, Scholl, & Forster, 2009;Lukkes, Vuong, Scholl, Oliver, & Forster, 2009;Weiss, Pryce, Jongen-Rêlo, Nanz-Bahr, & Feldon, 2004). Thus, the current study used Long-Evans rats; a strain which tends to voluntarily consume alcohol under intermittent access conditions (Simms et al, 2008;Simms, Bito-Onon, Chatterjee, & Bartlett, 2010) and tends to achieve higher blood ethanol concentrations (BECs) when drinking similar amounts of ethanol compared to other outbred strains (Carnicella, Ron, & Barak, 2014).…”
Section: Introductionmentioning
confidence: 99%